2003
DOI: 10.1364/ao.42.002960
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic response of breast tumor oxygenation to hyperoxic respiratory challenge monitored with three oxygen-sensitive parameters

Abstract: The simultaneous measurement of three oxygen-sensitive parameters [arterial hemoglobin oxygen saturation (SaO2), tumor vascular-oxygenated hemoglobin concentration ([HbO2]), and tumor oxygen tension (pO2)] in response to hyperoxic respiratory challenge is demonstrated in rat breast tumors. The effects of two hyperoxic gases [oxygen and carbogen (5% CO2 and 95% O2)] were compared, by use of two groups of Fisher rats with subcutaneous 13762NF breast tumors implanted in pedicles on the foreback. Two different gas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
32
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 32 publications
16
32
0
Order By: Relevance
“…This mathematical model has been utilized well to explain our experimental animal studies (Liu et al 2000, Gu et al 2003, Kim et al 2003b. Moreover, it has been supported by computer simulations (Kim and Liu 2005) and phantom study (Kim and Liu 2004) that the bi-phasic or bi-exponential feature can be well present if both a slow and a fast perfusion of flow co-exist within the interrogated area or volume by the NIR source and detector.…”
Section: F Mrm In Ratsmentioning
confidence: 66%
See 2 more Smart Citations
“…This mathematical model has been utilized well to explain our experimental animal studies (Liu et al 2000, Gu et al 2003, Kim et al 2003b. Moreover, it has been supported by computer simulations (Kim and Liu 2005) and phantom study (Kim and Liu 2004) that the bi-phasic or bi-exponential feature can be well present if both a slow and a fast perfusion of flow co-exist within the interrogated area or volume by the NIR source and detector.…”
Section: F Mrm In Ratsmentioning
confidence: 66%
“…Due to the deep penetration depth and biochemical specificity of NIRS, it has been widely applied for quantitative measurements of cerebral oxygenation (Delpy andCope 1997, Yodh andBoas 2003) and blood oxygenation in muscles in vivo (Homma et al 1996). Recently, NIRS has been also used to monitor tumour vascular oxygenation with respect to interventions (Hull et al 1999, Liu et al 2000, Gu et al 2003. With notable exceptions (Chance 1997, Dehghani et al 2004, Shah et al 2004, NIRS currently lacks spatial resolution, and thus, the utility of global measurements requires validation, given the well-documented heterogeneity of tumour oxygenation.…”
Section: Y•••bdsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have used FREDOM to examine the effects of vascular targeting agents [36,267], vasoactive agents [215] and hyperoxic gases [10,200,[212][213][214][215][216][217][268][269][270]. We have shown that measurements are consistent with sequential determinations made using electrodes [271,272] and fiber optic probes (FOXY TM and OxyLite ) [201,216]. Repeat measurements are highly reproducible and generally quite stable in tumors under baseline conditions.…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 89%
“…Other modalities provide an indication of hypoxia [197,198]. In many cases, there is a desire to measure pO 2 directly and this may be achieved using polarographic electrodes [199,200], fiber optic probes [201], free radical probes with electron spin resonance (ESR) [191,202], or PFC probes with NMR [9,10], as described below.…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 99%